Advancements in Integrated Thermoelectric Power Generation and Water Desalination Technologies: A Comprehensive Review - Oranit Traisak; Pranjal Kumar; Sara Vahaji; Yihe Zhang; Abhijit Date (Energies)
This paper reviews recent advancements in integrated thermoelectric power generation and water desalination technologies, driven by the increasing global demand for electricity and freshwater. The growing population and reliance on fossil fuels for electricity generation pose challenges related to environmental pollution and resource depletion, necessitating the exploration of alternative energy sources and desalination techniques. While thermoelectric generators are capable of converting low-temperature thermal energy into electricity and desalination processes that can utilize low-temperature thermal energy, their effective integration remains largely unexplored. Currently available hybrid power and water systems, such as those combining conventional heat engine cycles (e.g., the Rankine and Kalina cycles) with reverse osmosis, multi-effect distillation, and humidification–dehumidification, are limited in effectively utilizing low-grade thermal energy for simultaneous power generation and desalination, while solid-state heat-to-work conversion technology, such as thermoelectric generators, have low heat-to-work conversion efficiency. This paper identifies a key research gap in the limited effective integration of thermoelectric generators and desalination, despite their complementary characteristics. The study highlights the potential of hybrid systems, which leverage low-grade thermal energy for simultaneous power generation and desalination. The review also explores emerging material innovations in high figure of merit thermoelectric materials and advanced MD membranes, which could significantly enhance system performance. Furthermore, hybrid power–desalination systems incorporating thermoelectric generators with concentrated photovoltaic cells, solar thermal collectors, geothermal energy, and organic Rankine cycles (ORCs) are examined to highlight their potential for sustainable energy and water production. The findings underscore the importance of optimizing material properties, system configurations, and operating conditions to maximize efficiency and output while reducing economic and environmental costs.